1995
DOI: 10.1111/j.1467-6494.1995.tb00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences In Experiment Participation: Structure, Autonomy, and the Time of the Semeste

Abstract: This research investigated the association of two individual difference moderators of psychological phenomena with the time of semester students choose to participate in experiments. The Personal Need for Stmcture (PNS) scale and the Stein Self-Descriptioti Questionnaire were administered to the students in an introductory psychology class at the beginning of a university semester. Students' responses on these measures were related to their chosen dates of required participation in psychological research. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
1
29
1
1
Order By: Relevance
“…In contrast, because less creative personalities perform better when there is structure and reduced ambiguity, the opportunity to conform may be desirable since the group's expectations are clear (Judge, Thoreson, Pucik & Welbourne, 1999;Norton, 1975;Roman et al, 1995). For example, Neulinger (1965) reported that less creative personalities reported enjoying an unpleasant task more when they were forced to perform it than when they were given a choice.…”
Section: Conformity Pressure and Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, because less creative personalities perform better when there is structure and reduced ambiguity, the opportunity to conform may be desirable since the group's expectations are clear (Judge, Thoreson, Pucik & Welbourne, 1999;Norton, 1975;Roman et al, 1995). For example, Neulinger (1965) reported that less creative personalities reported enjoying an unpleasant task more when they were forced to perform it than when they were given a choice.…”
Section: Conformity Pressure and Creativitymentioning
confidence: 99%
“…In this context, pressure to conform might be experienced as an unduly controlling external constraint that may curtail idea expression (Amabile, Golfarb & Brackfield, 1990). Taken together, in groups composed of highly creative personalities, an individualistic norm should promote greater creativity when pressure to conform is low rather than high.In contrast, because less creative personalities perform better when there is structure and reduced ambiguity, the opportunity to conform may be desirable since the group's expectations are clear (Judge, Thoreson, Pucik & Welbourne, 1999;Norton, 1975;Roman et al, 1995). For example, Neulinger (1965) reported that less creative personalities reported enjoying an unpleasant task more when they were forced to perform it than when they were given a choice.…”
mentioning
confidence: 99%
“…Lower in personal need for structure; more indifferent or hostile to authority. Roman et al (1995) 4. Higher in sensation-seeking and impulsivity.…”
Section: Table 1 Differences In Personality and Task Performance Betwmentioning
confidence: 99%
“…Table 1 summarizes the major differences that have been found between students who choose to participate later versus earlier in an academic term. Given this potential for self-selection bias in a researcher's sample, some researchers have expressed concern that the effects of particular variables could depend on when during a term the participants were recruited (see, e.g., Harber et al, 2003;Roman et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation